1979
DOI: 10.1002/ajpa.1330510109
|View full text |Cite
|
Sign up to set email alerts
|

A correlation of tooth wear and age among modern Igloolik Eskimos

Abstract: The level of molar wear can be estimated reliably by measuring the cusp height. A correlation between age and the level of molar wear, expressed by a normalizing index (TWI) of cusp height, was found to exist in a sample of modern Igloolik Northwest Territories Eskimos. Not only was it possible to derive linear regression models to test the degree of correlation in the sample of 46 female and 39 male maxillary casts of Igloolik Eskimos, but the models were capable of accurately predicting the age of natives of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
1
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(67 citation statements)
references
References 11 publications
2
61
1
1
Order By: Relevance
“…Among the quantification methods of occlusal wear applicable to a cross-sectional study are qualitative ones which give a score following subjective criteria (e.g., Murphy, 1959;Molnar, 1971), and quantitative ones such as crown height (Tomenchuk and Mayhall, 1979;Kieser et al, 1985;Walker et al, 1991), ratio of area of exposed dentin to that of occlusal surface (Behrend, 1977;Walker, 1978;Richards, 1984;Richards and Miller, 1991), and ratio of worn area to that of occlusal surface (Molnar et al, 1983). Although the methods utilizing area have an advantage in accuracy, they can evaluate only a part of the entire wear process, depending on the subject to be measured.…”
Section: Occlusal Wearmentioning
confidence: 99%
“…Among the quantification methods of occlusal wear applicable to a cross-sectional study are qualitative ones which give a score following subjective criteria (e.g., Murphy, 1959;Molnar, 1971), and quantitative ones such as crown height (Tomenchuk and Mayhall, 1979;Kieser et al, 1985;Walker et al, 1991), ratio of area of exposed dentin to that of occlusal surface (Behrend, 1977;Walker, 1978;Richards, 1984;Richards and Miller, 1991), and ratio of worn area to that of occlusal surface (Molnar et al, 1983). Although the methods utilizing area have an advantage in accuracy, they can evaluate only a part of the entire wear process, depending on the subject to be measured.…”
Section: Occlusal Wearmentioning
confidence: 99%
“…Molnar (1971) suggested that differences in roles between the sexes conditioned the types of food consumed, with women consuming greater amounts of fibrous plants and abrasive roots they collect. Nonetheless, Tomenchuk and Mayhall (1979) reported that Canadian Igloolik Eskimo men exhibited greater wear rates in maxillary teeth than did women, likely caused by prolonged or heavier mastication. However, another study on the same population, based on the quantitative analysis of the percentage of dentin exposure , reported that the wear of anterior teeth in females highly exceeded that in males, up to the first premolar, and the differences were more pronounced in the maxillary dentition.…”
Section: Page 4 Of 30mentioning
confidence: 99%
“…Diet: meat-based. Sexual division of labor: strong but not focused on subsistence (men are the only food providers; Costa, 1977;Tomenchuk and Mayhall, 1979). M a n u s c r i p t 7 Dietary differences: low (Costa, 1977).…”
Section: Dealing With Age Effectsmentioning
confidence: 99%
See 2 more Smart Citations